Colored television: American religion gone global - Frederick, Marla Faye (Race religion, 2016)
"Jamaica, land we love" -- Religious dandyism : prosperity and performance in Black televangelism -- Relative prosperity : lived religion in the "dying field" -- Female televangelists and the gospel of sexual redemption -- Redeeming sexuality -- Distributing the message : globalization and the spread of Black televangelism -- Conclusion : voices of the next generation